PROPHYLACTIC EFFICACY OF VACCINATION AGAINST PNEUMOCOCCAL INFECTION IN CHILDREN WITH CHRONIC ADENOTONSILLAR DISEASES - S. N. Beniova; S. V. Taranova; A. L. Sizonenko; S. V. Babko (LLC "Diagnostics and Vaccines", 2015)
The article presents the results of study of clinical and immunological effectiveness of the application of the vaccine «Pneumo-23» for children of 3-7 years old, suffering from chronic nasopharyngeal ring diseases of pneumococcal etiology. The authors revealed reduction of the frequency of cases of the main disease exacerbation and cases of ARI adjoining. Reduction of the main clinical symptoms of chronic adenoiditis and chronic tonsillitis was registered. Number of specific IgMand IgGAT to PS of the vaccine doubled reliably.